KNOWLEDGE, ATTITUDES AND PERCEPTIONS OF PROSTATE CANCER AMONG MALE UNIVERSITY STUDENTS IN SOUTH AFRICA. - Thembane , Nokukhanya; Dlamini, Portia Nombulelo (Student's Journal of Health Research Africa, 2023)
Background: The aim of this study was to investigate the level of knowledge, attitudes, and practices regarding prostate cancer among male university students in South Africa. Prostate cancer is the most commonly diagnosed cancer among men worldwide, and early detection is key to successful treatment. However, knowledge gaps and misconceptions regarding prostate cancer can hinder early detection and treatment. Methods: The study adopted a cross-sectional design and collected data using a structured questionnaire. The questionnaire covered the risk factors, symptoms, prevention, and screening of prostate cancer. Results: The results of the study revealed that while 92.3% of the participants had heard of prostate cancer, only 69.6% had acceptable knowledge on the symptoms of the disease, and 84.6% believed that prostate cancer could be prevented. This suggests that while there is a general awareness of prostate cancer among male university students in South Africa, there are significant knowledge gaps regarding the disease. Additionally, family history, alcohol consumption, and smoking were identified as major risk factors for prostate cancer. However, there was a screening knowledge gap among the respondents, as only 32.3% were aware of prostate-specific antigen (PSA) testing, which is a common screening method for prostate cancer. Conclusion: In conclusion, this study highlights the need for increased education and awareness about prostate cancer among male university students in South Africa. The findings suggest that there are significant knowledge gaps regarding the disease, particularly regarding screening and family history. The study findings can be useful in developing targeted health interventions aimed at reducing the burden of prostate cancer among young men. Recommendation: The findings suggest that more attention should be given to educating young men on the symptoms, risk factors, and prevention of prostate cancer.